(untitled) (Pedagogical Horizons, 2021)
Interreligious learning processes claim to reduce prejudices, but at the same time it can be asked to what extent prejudices are sufficiently considered in the aims and organization of interreligious learning processes. Based on socio-psychological findings on the distribution of and reasons for prejudices, some aspects are explored as to what impact the consideration of prejudices can have on interreligious learning. The preconditions and aims of interreligious learning are considered as well as aspects of the implementation of interreligious learning. Here, the development of communication spaces about prejudices as well as sensitivity in the implementation of learning in encounter are discussed before emphasising the consideration of belonging, emotions as well as power and dominance imbalances in interreligious learning processes.